2002
DOI: 10.1007/bf02857665
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory effect of Bcl-2 family proteins in CPB-induced cardiomyocyte apoptosis in dog hearts

Abstract: Whether conventional hypothermic CPB induces myocyte apoptosis in dog hearts and modulation of bcl-2, bcl-xl, bax, bad, and caspase-3 pathways in this setting was investigated. Ten healthy adult dogs were randomized into sham-operated and CPB groups. Samples of left ventricle were obtained before, during and 3 h after CPB. In situ TUNEL was used to detect apoptotic myocytes. Immunohistochemistry and flow cytometry were employed for detection of expressions of bcl-2, bcl-xl, bax and bad proteins. Z-DEVD-AMC sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Accumulating studies have shown that the pro-apoptotic (Bax) and anti-apoptotic (Bcl-2) proteins of the Bcl-2 family play a pivotal role in this apoptotic process [38] The balance between pro- and anti-apoptotic members of the Bcl-2 family is critical in determining cell fate. Apart from their localization at the mitochondria and the cytoplasm, Bcl-2 and Bax proteins are also constitutionally present on the sarcolemma of the cardiomyocytes [39]. Currently, the anti-apoptotic role of cytosolic Bcl-2 in postconditioning cardioprotection has been well investigated in both in vivo and in vitro [38, 40], but little is known regarding the role of Bcl-2 family members in the sarcolemma and mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating studies have shown that the pro-apoptotic (Bax) and anti-apoptotic (Bcl-2) proteins of the Bcl-2 family play a pivotal role in this apoptotic process [38] The balance between pro- and anti-apoptotic members of the Bcl-2 family is critical in determining cell fate. Apart from their localization at the mitochondria and the cytoplasm, Bcl-2 and Bax proteins are also constitutionally present on the sarcolemma of the cardiomyocytes [39]. Currently, the anti-apoptotic role of cytosolic Bcl-2 in postconditioning cardioprotection has been well investigated in both in vivo and in vitro [38, 40], but little is known regarding the role of Bcl-2 family members in the sarcolemma and mitochondria.…”
Section: Discussionmentioning
confidence: 99%